EXPERIMENTAL VERIFICATION OF PERFORMANCE IMPROVEMENT OF RADAR DETECTION USING ROBUST WAVEFORM TECHNIQUES - Turekhanov, Anuar (Nazarbayev University School of Engineering and Digital Sciences, 2024)
This project was aimed at analyzing different methods of RADAR performance improvement and their efficiency in the experimental setting in mitigating noises and interferences in the received signal. The project will focus on the experimental results acquired from IWR1843BOOST 77 GHz electronic LFM RADAR and on the effect of different techniques on the object detection. Some of the techniques that were studied include increasing bandwidth for improved range resolution, frequency hopping, and interpolation in the STFT domain
Keywords: Type of access: Restricted; RADAR Detection; Robust Waveform Techniques